IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 82 TAHUN 2012 SEBAGAI UPAYA NEGARA MENCEGAH CYBERCRIME DALAM SISTEM TRANSAKSI ELEKTRONIK - Masitoh Indriani; Adhy Riadhy Arafah; Fitri Nuril Islamy (Yuridika, 2014)
The development of Information Technology (IT) changes the patterns of community’s behavior. The presence of the Internet as the main platform of online activities including electronic transaction is vulnerable to the presence of cyber attacks by irresponsible parties. Criminal acts in cyberspace (cybercrime) pose a major threat in the governance of online activities and other electronic transactions. One of the efforts of the Government of Republic of Indonesia to face those challenges is by authorising the Government Regulations Number 82 Year 2012 concerning the Implementation of Electronic Transaction Systems in order to govern the electronic transaction activities. This article will discuss about how the Government of Republic of Indonesia copes the issue of the threat on electronic transactions.Keywords: cybercrime, electronic transactions system, goverment regulation No. 82/ 2012